Adsorption and Desorption of Single‐Stranded DNA from Single‐Walled Carbon Nanotubes. Issue 13 (12th May 2017) - Shearer, Cameron J.; Yu, LePing; Fenati, Renzo; Sibley, Alexander J.; Quinton, Jamie S.; Gibson, Christopher T.; Ellis, Amanda V.; Andersson, Gunther G.; Shapter, Joseph G.
Abstract: The chemical affinity of single‐stranded DNA (ssDNA) to adsorb to the surface of single‐walled carbon nanotubes (SWCNTs) is used for SWCNT purification, separation and in bio‐devices. Despite the popularity of research on SWCNT‐ssDNA conjugates, very little work has studied the removal of adsorbed ssDNA on SWCNTs. This paper reports a comprehensive study of biological, physical and chemical treatments for the removal of ssDNA from SWCNT‐ssDNA suspensions. These include enzymatic cleavage, heat treatment under vacuum up to 400 °C, chemical treatments with high or low pH, oxidizing conditions, and high‐ionic‐strength solvents. Complimentary characterization techniques including fluorescence from a DNA‐intercalating dye (YO‐PRO‐1) and photoelectron spectroscopy are used to exhaustively study and compare the methods investigated. Enzyme treatment is found to remove the phosphate backbone only, leaving nucleosides adsorbed to SWCNTs. Heating in inert atmosphere is ineffective at removing ssDNA. Acid, base and oxidative treatment are found to be effective for the removal of ssDNA from SWCNTs. Where possible the mechanism of desorption is described and from the findings suggestions for "best practices" are provided. Abstract : Carbon nanotubes and DNA are commonly hybridized for carbon nanotube purification. Methods are developed to remove single stranded DNA from single walled carbon nanotubes. Enzyme treatment with exonuclease 1 achieves phosphodiester cleavage but nucleosides remain adsorbed. It is found that hydrolytic and oxidative chemical treatments are the most promising.